Postural orthostatic tachycardia syndrome and other related dysautonomic disorders after SARS-CoV-2 infection and after COVID-19 messenger RNA vaccination - Gómez-Moyano, Elisabeth; Rodríguez-Capitán, Jorge; Gaitán Román, Daniel; Reyes Bueno, José Antonio; Villalobos Sánchez, Aurora; Espíldora Hernández, Francisco; González Angulo, Gracia Eugenia; Molina Mora, María José; Thurnhofer-Hemsi, Karl; Molina-Ramos, Ana Isabel; Romero-Cuevas, Miguel; Jiménez-Navarro, Manuel; et al. (Frontiers in Neurology, 2023)
The COVID-19 pandemic has caused a challenge for our society due to the post-acute sequelae of the disease. Persistent symptoms and long-term multiorgan complications, known as Post-Acute COVID-19 Syndrome, can occur beyond 4 weeks from the onset of COVID-19 infection. Postural orthostatic tachycardia syndrome (POTS) is considered to be a variety of dysautonomia, which is characterized 2 This is a provisional file, not the final typeset article by chronic symptoms that occur with standing and a sustained increase in heart rate, without orthostatic hypotension. POTS can lead to debilitating symptoms, significant disability, and impaired quality of life. In this narrative review, the etiopathogenic basis, epidemiology, clinical manifestations, diagnosis, treatment, prognosis, and socio-economic impact of POTS, as well as other related dysautonomic disorders, after COVID-19 infection and SARS-CoV-2 postvaccination are discussed. After a search conducted in March 2023, a total of 89 relevant articles were selected from the PubMed, Google Scholar, and Web of Science databases. The review highlights the importance of recognizing and managing POTS after COVID-19 infection and vaccination, and the approach to autonomic disorders should be known by all specialists in different medical areas. The diagnosis of POTS requires a comprehensive clinical assessment, including a detailed medical history, physical examination, orthostatic vital signs, and autonomic function tests. The treatment of POTS after COVID-19 infection or vaccination is mainly focused on lifestyle modifications, such as increased fluid and salt intake, exercise, and graduated compression stockings. Pharmacotherapy, such as beta-blockers, fludrocortisone, midodrine, and ivabradine, may also be used in selected cases. Further research is needed to understand the underlying mechanisms, risk factors, and optimal treatment strategies for this complication.